Environment in the Courtroom, Volume II - Lucas, Alastair; Ingelson, Allan E. (University of Calgary Press, 2023)
Courts, regulatory tribunals, and international bodies are often seen as a last line of defense for environmental protection. Governmental bodies at the national and provincial level enact and enforce environmental law, and their decisions and actions are the focus of public attention and debate. Court and tribunal decisions may have significant effects on environmental outcomes, corporate practices, and raise questions of how they may best be effectively and efficiently enforced on an ongoing basis. Environment in the Courtroom, Volume II examines major contemporary environmental issues from an environmental law and policy perspective. Expanding and building upon the concepts explored in Environment in the Courtroom, it focuses on issues that have, or potentially could be, the subject of judicial and regulatory tribunal processes and decisions. This comprehensive work brings together leading environmental law and policy specialists to address the protection of the marine environment, issues in Canadian wildlife protection, and the enforcement of greenhouse gas emissions regulation. Drawing on a wide range of viewpoints, Environment in the Courtroom, Volume II asks specific questions about and provides detailed examination of Canada's international climate obligations, carbon pricing, trading and emissions regulations in oil production, agriculture, and international shipping, the protection of marine mammals and the marine environment, Indigenous rights to protect and manage wildlife, and much more. This is an essential book for students, scholars, and practitioners of environmental law.